2018
DOI: 10.3390/cancers10090305
|View full text |Cite
|
Sign up to set email alerts
|

Peroxiredoxin II Regulates Cancer Stem Cells and Stemness-Associated Properties of Cancers

Abstract: Cancer stem cells (CSCs) represent a sub-population of cancer cells with the ability to regulate stemness-associated properties which are specifically responsible for unlimited growth of cancers, generation of diverse cancer cells in differentiated state and resistance to existing chemotherapy and radiotherapy. Even though, current therapies destroy majority of cancer cells, it is believed to leave CSCs without eradicating which may be the conceptualization for chemoresistance and radio-resistance. Reactive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 116 publications
(207 reference statements)
0
16
0
Order By: Relevance
“…Recently, a growing number of studies have found that Prxs regulate their expression and activity, acting as oncogenes that promote carcinogenesis in various cancer types. In addition, Prxs are known to promote the cancer cell stemness [6971]. Nevertheless, as Prxs have also been shown to suppress tumorigenesis, more studies are required to verify the potential of Prxs as therapeutic targets in each cancer type.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a growing number of studies have found that Prxs regulate their expression and activity, acting as oncogenes that promote carcinogenesis in various cancer types. In addition, Prxs are known to promote the cancer cell stemness [6971]. Nevertheless, as Prxs have also been shown to suppress tumorigenesis, more studies are required to verify the potential of Prxs as therapeutic targets in each cancer type.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of SRY-related high-mobility-group-box protein-2 and octamer-binding transcription factor-4 was down-regulated in PRDX2-silenced Huh7-H-Ras G12V hepatoma cells, and sphere formation efficiency and epithelial-mesenchymal transition were significantly inhibited (6). Mechanistic studies showed that PRDX2 can regulate stemness of cancer stem cells through a variety of signaling pathways, which contribute to the maintenance of the cancer stem cell properties of hepatocellular carcinoma via VEGF/EGFR/STAT3 signaling and RAS/FOXM1 signaling (33)(34)(35). In the process of isolation and expansion of DMSCs, in vivo 34: 133-141 (2020) we found that knockout of PRDX2 can significantly inhibit the proliferation of stem cells with the increasing cell passage.…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of ROS causes damage to proteins, lipids and DNA and therefore irrecoverable damage to the cell [27]. Notably, cells have protection mechanisms from oxidative stress, including enzymatic antioxidants such as superoxide dismutase (SOD), catalases, TXN, peroxiredoxins, glutathione (GSH) peroxidases, p38-MAPK and sirtuins [57][58][59] and non-enzymatic molecules such as GSH, vitamin C (ascorbate), vitamin E (tocopherols) and polyphenols [60]. Interestingly, the administration of SOD-1 inhibitor, disulfiram, strongly counteracted breast CSCs expansion by modulating MAPK, NF-kB and STAT3 pathways [61,62].…”
Section: The Mitostemness: Fiction or Reality?mentioning
confidence: 99%